The approach of World Health Organization to articulate the role and assure impact of vaccines against antimicrobial resistance. Issue 6 (30th November 2022) - Frost, Isabel; Balachandran, Anand; Paulin-Deschenaux, Sarah; Sati, Hatim; Hasso-Agopsowicz, Mateusz
ABSTRACT: Antimicrobial resistance (AMR) is a growing global problem and there were an estimated 4.95 million deaths associated with bacterial AMR worldwide in 2019. Vaccines can impact AMR by preventing infections and reducing the need for antibiotics which will inadvertently slow the emergence of AMR. Effective infection prevention and control (IPC) has been identified as the cornerstone action to combat AMR by the World Health Assembly and the Global Action plan on AMR. Similarly, the Immunization Agenda 2030 highlights vaccines as critical tools to combat AMR. This article summarizes the strategy of the World Health Organization to understand, articulate and communicate the important role of vaccines in countering AMR. The work is organized around developing a strategy, understanding the pipeline of vaccines in development, articulating the value of vaccines against AMR, and assuring sustainable impact of vaccines at a country level to combat AMR.